Clinical Practice Guidelines for Unstable Angina Treatment. - Juan José Navarro López; Claudio Manuel González Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Unstable Angina Treatment. It has been defined as the oppressive pain or uneasiness mainly thoracic, which is caused by a transitory myocardial ischemia. This document includes important aspects as classification, diagnosis, treatment (aimed at its principal strategies) and risk stratification. It includes assessment guidelines focused on the most important aspects to be accomplished.